Immediate-Early-Gene (IEG) expression in excitotoxicity - Rogers, Annamarie (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2004)
The mouse cerebellar granule cell system (mCGCs; Schousboe et al, 1989) was established in this laboratory (Bayer AG, Germany) as a suitable cell culture model for excitotoxicity studies. Suitability was confirmed by MTT-based cytotoxicity, which was induced by glutamate (Glu) receptor agonists and inhibited by NMDA receptor antagonists (APS), but not by antagonists of the non-NMDA receptor subtype (CNQX).
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin